Social representations of school principals with respect to rural education - Gómez Melo, Danilo Andrés; Gómez Viasus, Johana Lorena (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The research article analyzes the social representations of school principals regarding rural education. Five rectors working in public educational institutions in the municipalities of Socha and Socotá, Boyacá participated in the study. The qualitative hermeneutic research adopts the processual approach of the theory of Social Representations, as a way of reading and understanding the information. The analysis revealed the Social Representations on rural education which, according to the scenario of enunciation, acquired meaning in the categories: access and accessibility, colonizing look, daily life and possibilities of rural education, as a source of knowledge of the educational reality. All of this was defined from the point of view of the teachers' directors.